Standardization of Golden Sea Cucumber (Stichopus hermanii) Extracts from Pelapis Island, Kayong Regency, West Kalimantan - Rusmini, Rusmini; Taurina, Wintari; Andrie, Mohamad (Biology, Medicine, & Natural Product Chemistry, 2023)
Stichopus hermanii can be used as a medicinal material, a source of animal protein, and wound healing medicine products. Extracts as raw materials for products must go through a standardization process to ensure pharmaceutical reproducibility, a therapeutic quality, and to ensure a consistent and uniform final composition. The purpose of this research was to determine the test results of the standardization parameters of Stichopus hermanii extract from Pelapis Island, West Kalimantan as raw material for wound healing herbal medicinal preparations. Preparation of extracts using the maceration method with 96% ethanol. The extract was standardized with specific parameters, including organoleptic, water and ethanol soluble content, phytochemical screening, and protein content, and non-specific parameters, including drying shrinkage, water content, ash content, and acid insoluble ash content. The test results obtained were a water-soluble content of 61.89%, ethanol-soluble content of 41.81%, protein content of 7.62%, drying shrinkage of 38.81%, water content of 20.58%, ash content of 37.95%, and acid insoluble ash content of 2.07%.